Changes of motor corticobulbar projections following different lesion types affecting the central nervous system in adult macaque monkeys. (16th August 2018) - Fregosi, Michela; Contestabile, Alessandro; Badoud, Simon; Borgognon, Simon; Cottet, Jérôme; Brunet, Jean‐François; Bloch, Jocelyne; Schwab, Martin E.; Rouiller, Eric M.
Abstract: Functional recovery from central nervous system injury is likely to be partly due to a rearrangement of neural circuits. In this context, the corticobulbar (corticoreticular) motor projections onto different nuclei of the ponto‐medullary reticular formation (PMRF) were investigated in 13 adult macaque monkeys after either, primary motor cortex injury (MCI) in the hand area, or spinal cord injury (SCI) or Parkinson's disease‐like lesions of the nigro‐striatal dopaminergic system (PD). A subgroup of animals in both MCI and SCI groups was treated with neurite growth promoting anti‐Nogo‐A antibodies, whereas all PD animals were treated with autologous neural cell ecosystems (ANCE). The anterograde tracer BDA was injected either in the premotor cortex (PM) or in the primary motor cortex (M1) to label and quantify corticobulbar axonal boutons terminaux and en passant in PMRF. As compared to intact animals, after MCI the density of corticobulbar projections from PM was strongly reduced but maintained their laterality dominance (ipsilateral), both in the presence or absence of anti‐Nogo‐A antibody treatment. In contrast, the density of corticobulbar projections from M1 was increased following opposite hemi‐section of the cervical cord (at C7 level) and anti‐Nogo‐A antibody treatment, with maintenance of contralateral laterality bias. In PD monkeys, the density of corticobulbar projections from PM was strongly reduced, as well as that from M1, but to a lesser extent. In conclusion, the densities of corticobulbar projections from PM or M1 were affected in a variable manner, depending on the type of lesion/pathology and the treatment aimed to enhance functional recovery. Abstract : In intact adult macaques, the corticobulbar projections are denser when originating from PM than from M1. After unilateral lesion of M1, the projection from the ipsilesional PM was strongly reduced, both in presence or absence of anti‐Nogo‐A antibody treatment. After 1‐methyl‐4phenyl‐1, 2, 3, 6‐tetrahydropyridine (MPTP) lesion (and following cell therapy), the projections from both PM and M1 also decreased. In contrast, after cervical cord hemi‐section, the projection from M1 increased, but only in presence of anti‐Nogo‐A antibody treatment.